2023
DOI: 10.3390/ijms241310682
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation of Genes Participating in Hepatic Metabolisms and Function in Fetal Calf Liver Is Altered by Maternal Undernutrition during Gestation

Abstract: This study aimed to elucidate the effects of maternal undernutrition (MUN) on epigenetic modification of hepatic genes in Japanese Black fetal calves during gestation. Using a previously established experimental design feeding the dams with 60% (LN) or 120% (HN) of their global nutritional requirements during the 8.5-month gestational period, DNA methylation in the fetal liver was analyzed with reduced representation bisulfite sequencing (RRBS). The promoters and gene bodies in the LN fetuses were hypomethylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 90 publications
(123 reference statements)
0
2
0
Order By: Relevance
“…The critical role of ECM in maintaining tissue integrity and facilitating cellular communication [ 46 ], combined with the PI3K-Akt pathway’s involvement in metabolic regulation [ 47 ], reflect a multifaceted approach to preserving cellular homeostasis. Recent studies add context to these findings: one showed that promoter hypomethylation related to maternal undernutrition was frequently observed in genes that participate in the PI3K-Akt signaling pathway and in some other ways, such as thyroid hormone signaling, Ras/Rap1 signaling, cAMP signaling, fatty acid metabolism, and cholesterol metabolism [ 28 ]. Moreover, another study identified skeletal muscle genes involved in the PI3K/Akt pathway as being significantly influenced by maternal protein supplementation during mid-gestation [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The critical role of ECM in maintaining tissue integrity and facilitating cellular communication [ 46 ], combined with the PI3K-Akt pathway’s involvement in metabolic regulation [ 47 ], reflect a multifaceted approach to preserving cellular homeostasis. Recent studies add context to these findings: one showed that promoter hypomethylation related to maternal undernutrition was frequently observed in genes that participate in the PI3K-Akt signaling pathway and in some other ways, such as thyroid hormone signaling, Ras/Rap1 signaling, cAMP signaling, fatty acid metabolism, and cholesterol metabolism [ 28 ]. Moreover, another study identified skeletal muscle genes involved in the PI3K/Akt pathway as being significantly influenced by maternal protein supplementation during mid-gestation [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Diniz et al [ 27 ] found that administering vitamin and mineral supplements from at least 71 days before breeding until day 83 of gestation influences fetal hepatic function by changing the expression of genes associated with energy and lipid metabolism. Another study on maternal undernutrition in fetal calves demonstrated that calves whose mothers were fed 60% of their nutritional requirements exhibited significant hypomethylation in liver genes compared to those fed 120% [ 28 ]. These studies underline the important influence of maternal nutrition on fetal liver gene expression, emphasizing how dietary variations during pregnancy can significantly shape the developmental and metabolic pathways in offspring.…”
Section: Introductionmentioning
confidence: 99%